Emtea nakliyat sigortaları - Aygören, Emine (My University, 2005)
Uluslararasındaki teknolojik ve ekonomik gelişmeler hukuk alanında da etkisini göstermekte, milli hukukların tek başına ve birbirinden farklı çözümler üretmesi yerine, nakliyatla ilgili hukuki sorunların uluslararası düzenlemelerle çözülmesi beklentisi ortaya çıkmaktadır. Türk Emtea Nakliyat Poliçesi Genel Şartlarının Londra Sigortacılar Birliği Emtea Klozlarının etkisi altında kaldığı saptanmış; ve gerek teminat kapsamı açısından ve gerekse deniz rizikolarının tasnifi bakımından 1906 tarihli İngiliz Deniz Nakliyat Sigorta Kanununun ülkemizde mer'i bir kanunmuş gibi, Emtea Nakliyat Sigortacılığımız üzerinde geniş ölçüde etki ettiği görülmüştür. Türk Ticaret Kanunu'nun SİGORTA HUKUKU başlığını taşıyan kitabının 1263/ 1. maddesi hükmünde ....para ile ölçülebilir nitelikte menfaatin olmasının gerekliliği vurgulanmaktadır. Bir sigorta mukavelesinde, kanunun öngördüğü ve taraflarca kararlaştırılabilen rizikolara karşı sigortalanan menfaatin, ekonomik bir değer olarak Emtea olduğu ihtimallerde, söz konusu, sigorta mukavelesinin Emtea nakliyat sigortasının tarihi gelişimi, kaynağı himayesi Türk Emtea Nakliyat Sigortası Genel Şartları, İngiliz Enstitü Yük Klozları detaylı olarak incelenmiştir. Birinci bölümde, Emtea sigortasının tarihi gelişimi bugünkü önemi ve zorunluluğu bazı temel kavramlar üzerinde durulmuş Emtea hasarları ve tazminat belirlenmesi, örneklerle ve bazı yargı kararıyla sunulmaya çalışılmıştır. Bu bakımdan Emtea Nakliyat Sigortası İç Hukuk, İngiliz Hukuku ve Uluslararası klozlar dışında Türk Sigortacılık Sektöründeki uygulama ile sigortacılık alanında araştırma yapan teorisyen bilim adamlarının eserlerine yapılan atıflarla teori ve uygulama zaman zaman Yargı kararıyla sunulmuştur. İkinci bölümde ele alınan Türk Emtea Nakliyat Sigortası Genel Şartları maddeler halinde incelenmiş ve maddelerin hükümleri açıklanarak Türk Yargı kararlarından konuya ilişkin örneklerle tetkik edilmiştir. Üçüncü ve son bölümde ise Emtea Nakliyat sigortası ile yapılan değerlendirmeler, Londra Sigortacılık Enstitüsü tarafından hazırlanan 01.01.1963 ve 01.01.1982 tarihli kloz takımları ağırlıklı olarak incelenmiş, kloz takımlarındaki hükümlerin tercümelerine yer verilmiş, kloz takımlarının sağladığı himaye karşılaştırılmalı olarak incelenmiştir.

Developments in technology and economics in international aspect had impact on the legal sphere, hence It is usually expected that the legal problems regarding shipping(transportation) should be solved out by international regulations rather than the national laws producing solutions by their own which varies from each other. It has been explored that the General Rules of the Turkish Commodity Shipping Policy have been under the influence of the clauses of the Insurers Association of London. In terms of enclosure of guaranty and also the classification of sea risks, our Commodity Shipping Insurance has been widely affected by The British Code of Insurance for Sea Transportation in 1906 as if the latter was officially operating in our country. The provision of article 1263/ 1 of the section entitled 'Insurance Law' in the Turkish Commercial Code points out the necessity of existence of benefit measurable with money. In an insurance policy, the following subjects have been examined in detail: Possibilities of benefits, which are insured in an insurance policy against the risks foreseen by the law and decided by the parties, to become a commodity as an economic value; the historical evolution and origin of commodity shipping insurance, insurance policy and insurance contract; the general rules of the Turkish Commodity Shipping Insurance, and finally the freight clauses of the British Institute. The first chapter deals with the historical evolution of commodity insurance, its current importance and necessity, and also a number of basic terms. In this chapter, it is also attempted to present the damages occurred in the goods and determination of compensation through cases and several legal verdicts. In this regard, apart from clauses of domestic law, British law and international laws about the Commodity Shipping Insurance, practices in the Turkish insurance sector and references to the theoretical works of the authors who work in legal theory have been also presented in this chapter, sometimes with the legal verdicts. In the second chapter, the general rules of the Turkish Commodity Insurance have been examined article by article and also the legal judgments of the articles have been explained and analyzed through the related examples from the cases in the Turkish Judiciary. The third and final chapter has examined the assessments regarding the Commodity Shipping Insurance as well as the clause series prepared by the London Insurance Institute dated 01.01.1963 and 01.01.1982, translations of provisions of Clauses have been rendered and Protection provided by the Clause series has been examined comparatively.
Keywords: Sigorta; Sigortacılık; Taşıma sırasında hasar ve kayıp sigortası